The educational program of a magistracy for economic direction of preparation in new coordinates of development: conceptual elements - V. F. Potudanskaya; E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность")
From a position of the new interconnected development coordinates in the form of FGOS VO(3++) and professional standards the maintenance of the basic conceptual elements of development of the educational program of a magistracy in the economy direction 38.04.01 reveals: compliance of contents of the planned educational program to requirements of FGOS VO(3++); formation of competencebased model of the graduate taking into account professional standards; compliance of the educational program to the priority directions of development of economy of the Omsk region, to requirements of employers and the development strategy of basic higher education institution of the region — OMGTU; increase in appeal of the educational program in education market; a possibility of use of the educational program at network interaction of higher education institutions; use of progressive methods of training (including design, praktiko-focused and so forth); development of system of independent estimation of competences of undergraduates on the basis of public professional accreditation; possibility of construction and realization of individual educational trajectories; ensuring the integrated interrelation of educational programs of a bachelor degree and a magistracy. The purpose of creation of similar programs, implementation of the concept of the modernized education in the direction of preparation of a magistracy 38.04.01 «Economy» is